The New Testament and Hellenistic Judaism - Borgen, Peder; Giversen, Soren (Peabody, MA Hendrickson, 1997)
Includes bibliographical references and indexes.
Papers read at a conference at the Faculty of Theology, University of Aarhus, Feb. 8-10, 1992.
Keywords: Judaism -- history -- post-exilic period, 586 B.C.-210 A.D. -- congresses; Judaism -- relations -- Christianity -- congresses; Christianity and other religions -- Judaism -- congresses; Church history -- primitive and early church, ca. 30-600 -- congresses; Bible. N.T. -- criticism, interpretation, etc. -- congresses